Unworried : a life without anxiety - Popcak, Gregory K. (Our Sunday Visitor, 2018)
Anxiety. It's practically an epidemic. Twenty percent of Americans suffer from anxiety disorders, and millions more wrestle with worry and stress on a daily basis. For us as Christians, all that worry gets mixed up with a lot of guilt. After all, Scripture tells us, "Have no anxiety at all" (Phil 4:6). How can we stop worrying and start living an anxiety-free life? As you'll learn in Unworried: A Life Without Anxiety, the answer isn't "just pray more" or "just read more Scripture" or, worst of all, "just stop worrying." If we learn to respect how God made us, we can build new habits of thinking.